2023
DOI: 10.1111/os.13774
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Major Swelling Grade Affects the Clinical Outcomes after OLIF: A Retrospective Study of 89 Patients

Abstract: ObjectsOblique lumbar interbody fusion (OLIF) has gained increasing popularity recently. However, complications resulting from intraoperative retraction of psoas major (PM) sometimes occur. The aim of this study is to evaluate the degree of PM swelling by developing a scoring system called the Psoas Major Swelling Grade (PMSG), and to investigate the correlation between the PMSG and clinical outcomes after OLIF.MethodsPatients who underwent L4‐5 OLIF at our hospital from May 2019 to May 2021 were reviewed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The measurements were conducted by two experienced radiologists. Our preliminary study outcomes indicated that when the IH-G exceeds 50%, there is a marked increase in the risk of short-term postoperative complications 7 . Consequently, in this study, an IH-G greater than 50% is classi ed as the Severe Hematoma Group (SHG), while those below this threshold are considered the Common Hematoma Group (CHG).…”
Section: Imaging Indicatorsmentioning
confidence: 77%
See 1 more Smart Citation
“…The measurements were conducted by two experienced radiologists. Our preliminary study outcomes indicated that when the IH-G exceeds 50%, there is a marked increase in the risk of short-term postoperative complications 7 . Consequently, in this study, an IH-G greater than 50% is classi ed as the Severe Hematoma Group (SHG), while those below this threshold are considered the Common Hematoma Group (CHG).…”
Section: Imaging Indicatorsmentioning
confidence: 77%
“…entail undue expense without offering therapeutic advantages 7 . It is a challenging question to accurately re ect the Iliopsoas Hematoma-Grade(IH-G) during the postoperative management process surrounding OLIF.…”
mentioning
confidence: 99%